New prognostic markers of hearing impairment in children: gene-gene interaction and approximation models - L. P. Sydorchuk; O. M. Iftoda (Kazimierz Wielki University, 2020)
Objective: to evaluate the gene-gene interaction, assess the risks and develop some approximation models of hearing loss / deafness occurrence in children, depending on the genes polymorphism gab junction B2 (GJB2, rs80338939), and interleukin-4 (IL-4, rs 2243250) and other risk factors. Materials and methods: Study included 102 children with hearing impairment: 68 with sensorineural (SNHL) and 34 with conductive hearing loss (CHL), among them 36 (35.29%) girls and 66 (64.71%) boys. The patients' age vary from 8 to 18 yo (on the average 13.90±3.11 yo). Diagnosis set by otorhinolaryngology (ENT) methods: ENT examination, computer audiometry, impedancemetry, tympanometry. The control group included 60 practically healthy children: 22 girls (36.67%), 38 boys (63.33%). Polymorphism of GJB2 (rs80338939) and IL-4 (rs 2243250) genes was studied by polymerase chain reaction method. Risk assessed by Relative Risk, Odds Ratio and 95% Confidential intervals. Results. The combination of 35delG / TT, as well as Non-Del / TT and 35delG/ TC genotypes in the genome is associated with a high risk of hearing loss in general children population (from 0.932 to 1.432; OR=19.5; p=0.003), as well as the appearance SNHL (from 0.765 to 1.765), stronger than the combination of unfavorable homozygotes TT / 35DelG - 1.765. The combination of homozygotes for the wild allele of both genes (especially CC / Non-Del) is associated with a low risk of deafness: hearing loss in general -1,068, for SNHL -0,908, for CHL -0,750 (p<0,01), for CC / 35delG combination, or TC / Non-Del: in general -0.068 -, and for SNHL -0.235 and -0.11 respectively, (p>0.05). Infectious diseases in anamnesis (meningitis, measles, mumps, or rubella) increases the likelihood of CHL by 9.41 times (OR=12.0; p=0.007). Concomitant chronic non-obstructive and obstructive upper and lower respiratory tract diseases increase the risk of both SNHL and CHL in children regardless of age: for SNHL 3.75-7.81 times (OR=6.50-10.9; p≤0.028-0.01), for CHL - 4.29-8.75 times (OR=6.19-12.9; p≤0.03-0.009). The revealed dependence of the indicators is best described by the logit-regression approximating models with high multiple correlation coefficient (R2=0.9761); low standard error of the model estimation (ε=0.1114); connection criterion F=124.2; degrees of freedom df=7.43 (p<0.001). Conclusions: Genes polymorphism's GJB2 (rs80338939) and IL-4 (rs 2243250) and their interactions are new prognostic markers of hearing impairment in children. Approximating models describe the likelihood of SNHL and CHL in observed population.